2006
DOI: 10.1002/cncr.21825
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of recurrence in encapsulated Hurthle cell carcinoma of the thyroid gland

Abstract: Objective Lower extremity functional performance and perception of functional abilities influence clinical management in people diagnosed with unilateral or bilateral knee osteoarthritis (OA). The purpose of this study was to determine if there were differences in perception of function and performance during functional tasks between individuals with unilateral and bilateral knee OA. Methods The functional abilities of patients with symptomatic and radiographic diagnosed unilateral (n = 84) or bilateral (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 16 publications
7
83
3
5
Order By: Relevance
“…Capsular invasion and vascular invasion were evaluated based on the categories in the textbook written by Chan [24], in which minimally invasive FTC was divided into three categories: with capsular invasion only, with limited (<4) vascular invasion, and with extensive (>4) vascular invasion. The cutoff number of vascular invasion was set at 4 based on the findings of previous studies [25][26][27]. Widely invasive FTC was defined as tumor with widespread invasion of adjacent thyroid tissue and/or blood vessels and such cases were not enrolled in this study under the diagnosis of our coauthor (M.H.).…”
Section: Resultsmentioning
confidence: 99%
“…Capsular invasion and vascular invasion were evaluated based on the categories in the textbook written by Chan [24], in which minimally invasive FTC was divided into three categories: with capsular invasion only, with limited (<4) vascular invasion, and with extensive (>4) vascular invasion. The cutoff number of vascular invasion was set at 4 based on the findings of previous studies [25][26][27]. Widely invasive FTC was defined as tumor with widespread invasion of adjacent thyroid tissue and/or blood vessels and such cases were not enrolled in this study under the diagnosis of our coauthor (M.H.).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have indicated that oncocytic carcinomas behave more aggressively compared to the usual variants of well differentiated thyroid cancers, and result in a higher incidence of metastases and a lower survival rate; hence they recommend an aggressive surgical treatment regime for all oncocytic follicular tumors [8][9][10]. On the other hand, other reports suggest that oncocytic follicular tumors are not more aggressive than their conventional counterparts [11][12][13].…”
Section: Thyroid Tissuesmentioning
confidence: 99%
“…Tumors with marked vascular invasion (more than 4 foci), high grade histology (increased mitoses and necrosis) and distant metastasis at presentation should be excluded from the borderline and WDA category, because their more aggressive nature was reported [10,12,23,24,[30][31][32][33][34]. Moderately differentiated follicular cell adenocarcinoma (MDA) included FTC with angioinvasion (more than 4) and aggressive PTC variants, such as tall cell, columnar cell, solid, loss of cellular polarity/cohesiveness (hobnail) variants and encapsulated carcinoma with high grade histology [8,9,20,[30][31][32][33][34][35]. PDC in our classification included PDC of WHO definition, insular carcinoma, tumors with minor anaplastic transformation, and cases with distant metastasis at presentation [8,9].…”
Section: The New Classification Of Thyroid Follicular Cell Tumorsmentioning
confidence: 99%
“…In brief, common type PTC was divided in two groups: WDA (PTC with invasion and/or nodal metastasis) and MDA (highrisk PTC, such as tall cell, columnar cell, solid, loss of cellular polarity/cohesiveness and hobnail variants) [8,9,11,20,21,35,[46][47][48][49]. FTC type carcinoma was also divided into two groups depending on invasiveness but it was modified in this review because of recent prognostic data [23,24,[30][31][32][33][34].…”
Section: Differentiation Classification Of Follicular Cell Carcinomasmentioning
confidence: 99%